THE EFFECT OF EYE-FOOT COORDINATION, FLEXIBILITY OF THE LIMBS, BODY BALANCE AND SELF-CONFIDENCE TO THE ACCURACY OF THE FOOTBALL OF SEPAK TAKRAW - Jufrianis Jufrianis; Akbar Akbar; James Tangkudung (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2018)
The purpose of this study was to obtain the effect of eye-foot coordination, flexibility of the limbs, body balance and self-confidence to the accuracy of the football of sepak takraw. The research method used in this research is the type of quantitative research with causality study approach. Technical Analysis uses a path analysis approach. Total population The study population is 40 athletes, sampling technique with total sampling. The number of samples in this study are 40 athletes who follow the Center for Student Development and Training. the results of this study conclude: (1) foot-eye coordination can directly affect the accuracy of the football on sepak takraw of 6.94% (2) limb formation can directly affect the accuracy of the football's early takraw of 5.96%, 3 ) the balance of the body can directly affect the initial accuracy of sepak takraw by 3.53%, (4) Self-confidence can directly affect the accuracy of the footballing of sepak takraw by 4.38%, (5) foot-eye coordination can affect direct self-confidence of 3.56%, (6) limb formation can directly influence self-confidence of 2.54%, (7) the balance of the body can directly affect self-confidence by 2.36%. Keywords: Foot-Coordination, Limb Formation, Body Balance, Self Confidence and Accuracy of Football Upper Sepak takraw.